On the production of 52gMn by deuteron irradiation on natural chromium and its radionuclidic purity. (December 2020) - Bianchi, Francesca; Marchi, Claudio; Fuad, Glara; Groppi, Flavia; Haddad, Férid; Magagnin, Luca; Manenti, Simone
Abstract: The positron emitter 52g Mn is used for the Positron Emission Tomography - PET imaging.In this work we investigate the nuclear reactions for production of 52g Mn and 54 Mn induced by deuteron beams on natural chromium targets at energies up to E d  = 28 MeV using the stacked-foils activation technique. We calculate the thick target yields for 52g Mn and for the radionuclidic impurity 54 Mn, and we compare the radionuclidic purity of 52g Mn with that achievable in proton activation of Cr. The cross-sections of the reactions nat Cr(d, pxn) 51 Cr and nat Cr(d, x) 48 V are also presented. Highlights: Cross-sections of the nat Cr (d, x) 52g Mn, 54 Mn, 51 Cr, and 48 V were measured up to 28 MeV. Production yield of 52g Mn and 54 Mn radionuclides was determined. Radionuclidic purity of 52g Mn was calculated. 52g Mn radionuclidic purity with deuteron beam was compared with the proton one.